EPIDEMIOLOGICAL STUDY OF COVID-19 IN A NORTHERN STATE OF BRAZIL - Gonçalves, Caio Willer Brito (2020)
The clinical disease called Covid-19 is caused by a new coronavirus, called SARS-CoV-2, which causes a Severe Acute Respiratory Syndrome. This study aimed to analyze epidemiological aspects of Covid-19 in the state of Tocantins. Cross-sectional, retrospective study with a quantitative and descriptive approach through consultation of the Ministry of Health database from March 18 to July 30, 2020. There were 24,824 reported cases, of which 60% have recovered , about 60% and there was a mortality rate of 1.5%. Regarding gender, the highest percentage was found in males (52.7%). Regarding the age group, there was a progressive increase in the incidence of involvement during the evolution of the age group until reaching the largest number of cases between 20 and 39 years of age, corresponding to 6300 cases. It is concluded that from the results presented, there is a progression in the number of cases, with prevalence for the economically active age group, and a greater number of deaths in the elderly. Thus, it is essential to continue prophylaxis measures to control the high transmission chain in the state of Tocantins.